UPLC-Q-TOF/MS, network pharmacology, molecular docking, and experimental validation to explore the mechanisms of toad clothing on rheumatoid arthritis - Ting Wang; Haixiong Xia; Jingyi Zhu; Mingyou Yu; Ziyi Zhang; Junhou Lu; Wei Zhou; Jianwei Xu (Scientific Reports)
Abstract Toad clothing (toad slough) detoxifies, reduces oedema and analgesia, is anti-inflammatory and anti-tumour, and regulates the immune system. Toad clothing’s mechanism is unclear. The molecular mechanism of toad clothing in rheumatoid arthritis (RA) therapy will be investigated in this research. We used Ultra-Performance Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry (UPLC-Q-TOF/MS), network pharmacology, molecular docking, and in vitro experiments to investigate the mechanism behind the anti-RA action of toad apparel. First, UPLC-Q-TOF/MS revealed 24 toad clothing ingredients. Network pharmacology predicted five key elements, six core targets, and the Phosphatidylinositol 3-Kinase/ Protein Kinase B (PI3K/AKT) signalling pathway. Then, molecular docking was used to validate the binding ability of core chemical constituents and core targets of toad clothing. The results showed that the primary constituent, resibufogenin, was bound tightly to six core targets and had a good affinity for key RA targets such as Phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), Epidermal Growth Factor Receptor (EGFR), and Janus Kinase 2 (JAK2). Cellular tests demonstrated that resibufogenin dramatically lowered Tumour Necrosis Factor-alpha (TNF-α), Interleukin-6 (IL-6), and Interleukin-1 beta (IL-1β) levels and regulated the PI3K/AKT signalling pathway. This research showed toad clothing’s anti-RA pharmacodynamic material basis and mechanism, offering a theoretical foundation for its creation, use, and clinical application.